Halal Label and Legality on Purchasing Decision: A Case Study of JacQue Products - Indriyaniali, Sri (Manunggal Halim Jaya, 2025)
This study aimed to assess the impact of halal labelling and legality on purchasing decisions for health drink goods, JaeQue, in the Lubuk Dalam District in 2023. The sampling formula was used to choose a sample of 100 responders. This is a quantitative research methodology, using data collected via a questionnaire. The determination coefficient (R2) analysis yielded 46.9%, with the remaining 53.1% explained by other variables. According to the F-test results, F-count>F-table (42.810>3.09), halal labelling and legality have a substantial effect on purchase decisions. If the T-test of halal labelling (X1) on purchase decisions (Y) is T-count < T-table (1.458 < 1.984), HO is accepted and H1 is rejected. This demonstrates that halal labelling has little influence on purchase decisions. If the T-test of legality (X2) on purchasing decisions (Y) is T-count>T-table (5.887>1.984), H2 is allowed, whereas HO is denied. This implies that there is a strong link between legality and purchase decisions.